The Enduring Legacy : Structured Inequality in America's Public Schools - Ryan, Mark, 1947- (Book collections on Project MUSE., 2020)
"The book outlines the historical, political and pedagogical reality of growing segregation and racial isolation in America's 21st century public schools. It explores the dialectic between the philosophies of inclusion and exclusion, examining an underlying contradiction: public education that continually postures to be ever more inclusive while simultaneously perpetuating an exclusive system through systematized discrimination to maintain inequality. The book concludes that undoing re-segregation is imperative to achieve social justice and a better education for all children"--